New evidence about the Palaeolithic peopling of the southern margin of the western Alps. The Colline novaresi area. (February 2022) - Daffara, Sara; García-Rojas, Maite; Berruti, Gabriele L.F.; Caracausi, Sandro; Gianella, Mauro A.; Ferrario, Massimo Monforti; Vanzi, Roberto; Mordeglia, Lucia I.
Highlights: Few data about Palaeolithic peopling are known in north-western Italy. The Colline novaresi area (Hills) has lithic assemblages found during nor systematic collections. A new research project has been set to investigate the Hills area. In the Hills area a Middle Palaeolithic, a Epigravettian, a Mesolithic and a Neolithic phase have been distinguished. The technological study of the lithic artefacts form the Hills provide data that reliable on a regional and sub-regional scale for what concerns raw material management and land mobility. Abstract: The Colline novaresi area is located in the north-eastern part of Piedmont. The hills are formed by moraine deposits and fluvio-glacial lithologies originating from Quaternary glacial events, which in turn were affected by a process of fluvial terraces. This area has been known for decades for the presence of archaeological sites, among which the most studied belong to a time span ranging from the Copper Age to the Iron Age. In the 1980′s, a Mesolithic lithic assemblage (Castelnovian) was found during investigation activities and was object of a techno-typological analysis. The present work, within the limits imposed by the non-systematic recovery of surface collections, deals with the techno-typological study of lithic artefacts collected in the Colline Novaresi area. The main aim is to highlight aspects of the technological behaviour of the hunter-gatherer's groups that inhabited the area, investigating the different exploitation strategies and the choices of the lithic resources. The absence of a stratigraphic context forces to base the identification of the different chronological horizons only on techno-typological criteria. Therefore, most of the lithic tools analysed remain indeterminate as far as this aspect is concerned, and sometimes only a generic distinction between Palaeolithic/Mesolithic and Neolithic is proposed. A most reliable chronological attribution is instead possible for retouched tools, Levallois cores and products and for laminar implements with clear technological attributes. The results obtained show that this area of Piedmont was inhabited during the Middle and Upper Palaeolithic, and an Epigravettian phase has also been recognized. A minority of the studied lithic tools refers to the Mesolithic. Considering that in the south-western margin of the alpine region the data on the Palaeolithic are very fragmentary, the technological study proposed here acquires importance in outlining a more precise scenario also for this part of the Italian peninsula.